A Systemic Review of Primary Malignant Long Bone Tumors in Children and Adolescents - Khan, M; Patel, R; Youssef, M; Banerjee, R; Pardiwala, A; Belen, C (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: Managing bone tumours is complex, relying on limited evidence, expert opinions, and retrospective reviews. Multidisciplinary approaches and early diagnosis are crucial for better outcomes, especially in young patients with growing skeletons. The aim of this systemic review and meta-analysis is to give a comprehensive review of common malignant tumors affecting long bones in children and adolescents. MATERIAL AND METHODS: A PubMed/Medline search for "primary malignant long bone tumours in children" initially retrieved 1120 papers, which were subsequently narrowed down to 110 articles based on inclusion and exclusion criteria. These articles were reviewed, focusing on clinical presentation, diagnostic workup, treatment options, surgical planning, and variations in presentation, including rare tumours. The two most commonly reported tumours were osteosarcoma and Ewing sarcoma, leading to the division of studies into five groups. The inclusion criteria encompassed malignancies in patients aged 2-25 years, work-up, imaging, surgical treatment, rare tumour case reports, and surgical management principles, resulting in a heterogeneous group of articles. To enhance categorisation, it was clarified that studies with 10 or more cases were considered retrospective reviews. RESULTS: Reviewing of results thus demonstrate that the two likely tumours in children under consideration were osteosarcoma and Ewing sarcoma. Their presentation findings and clinical features were discussed in detail in the review. It is worth noting here that in case of differential diagnosis this should be the first on the list. DISCUSSION AND CONCLUSIONS: Although focus of literature is more on the two most common tumours. However, rare tumours should be considered as they can mimic these common tumors. KEY WORDS: primary, malignant, bone tumors, children, adolescent.
Keywords: Adolescent; Child; lidé; Ewingův sarkom; Osteosarcoma; nádory kostí; Sarcoma, Ewing; dítě; předškolní dítě; osteosarkom; Bone Neoplasms; mladiství; Child, Preschool; Humans